Strait of Malacca and the Maritime Security: Safeties of the Regional Powers - Bibi, Hajra; Aimen, Um e; Farooq, Hina (Annals of Human and Social Sciences, 2024)
The Malacca strait, which links the pacific and Indian oceans, is vital to regional security and maritime trade. The security issues that the Malacca strait, one of the busiest and most significant maritime commerce routes in the world, faces and how these affect shipping stability both locally in Southeast Asia and internationally. In order to address the various issues surrounding marine security in the Malacca strait, this paper examines the interests and roles of both global and regional actors, including China, India and Japan as well as Indonesia, Malaysia and Singapore. It looks at how different parties cooperate and disagree as well as how well-suited current regional frameworks and international marine rules are to dealing with security challenges. In order to provide safe passage for international trade, maintain regional stability, and balance the interests of several stakeholders, this article suggests potential solutions and policy proposals for enhancing maritime security in the Malacca strait.